PENGARUH LKS DALAM MODEL PEMBELAJARAN CTL TERHADAP HASIL BELAJAR DAN KEMANDIRIAN BELAJAR SISWA PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Makharany Dalimunthe; Feri Andi Syuhada; Wilda Azwar; Junifa Layla Sihombing (Jurnal Guru Kita PGSD, 2020)
Abstract: INFLUENCE OF LKS IN CTL LEARNING MODEL TOWARDS LEARNING AND INDEPENDENCE LEARNING STUDENTS IN CHAPTER OF ELECTROLITE AND NON ELECTROLITE SOLUTION. This study aims to determine the effect of the LKS media in the CTL learning model on learning outcomes and student learning independence on electrolyte and non-electrolyte solution material. The sampling technique uses simple random sampling. This study uses a pretest-posttest control group design. Hypothesis testing uses independent samples t-test with the application of SPSS 21. The results of the study show: (1) test requirements analysis, the data are normally distributed and homogeneous; (2) hypothesis test I, significant (1-tailed) 0.1725> 0.05 then Ho is accepted; and (3) hypothesis test II, significant (1-tailed) 0.005 <0.05 then Ho is rejected. It can be concluded that the learning outcomes of students using the LKS media in the CTL learning model are not higher than the learning outcomes of students who are taught without using the LKS media in the CTL learning model on electrolyte and non electrolyte solution material, but the learning independence of students taught using the LKS media in the learning model CTL is higher than the independence of learning students who are taught without using the LKS media in the CTL learning model on the material electrolyte and non-electrolyte solutions.Keywords: LKS Media, CTL Learning Model, Student Learning Outcomes, Student Learning Independence, Electrolyte and Non-Electrolyte SolutionsAbstrak: PENGARUH LKS DALAM MODEL PEMBELAJARAN CTL TERHADAP HASIL BELAJAR DAN KEMANDIRIAN BELAJAR SISWA PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT. Penelitian ini bertujuan untuk mengetahui pengaruh media LKS dalam model pembelajaran CTL terhadap hasil belajar dan kemandirian belajar siswa pada materi larutan elektrolit dan non elektrolit. Teknik pengambilan sampel menggunakan sampling random sederhana. Penelitian ini menggunakan rancangan pretes postes control group design. Uji hipotesis menggunakan independent samples t-test dengan aplikasi SPSS 21. Hasil penelitian menunjukkan : (1) uji persyaratan analisis, data berdistribusi normal dan homogen; (2) uji hipotesis I, signifikan (1-tailed) 0,1725 > 0,05 maka Ho diterima;  dan (3) uji hipotesis II, signifikan (1-tailed) 0,005 < 0,05 maka Ho ditolak. Dapat disimpulkan bahwa hasil belajar siswa yang diajar menggunakan media LKS dalam model pembelajaran CTL tidak lebih tinggi daripada hasil belajar siswa yang diajar tanpa menggunakan media LKS dalam model pembelajaran CTL pada materi larutan elektrolit dan non elektrolit, tetapi kemandirian belajar siswa yang diajar menggunakan media LKS dalam model pembelajaran CTL lebih tinggi daripada kemandirian belajar siswa yang diajar tanpa menggunakan media LKS dalam model pembelajaran CTL pada materi larutan elektrolit dan non elektrolit. Kata kunci: Media LKS, Model Pembelajaran CTL, Hasil Belajar Siswa, Kemandirian Belajar Siswa, Larutan Elektrolit dan Non Elektrolit